Association of CD204+ macrophages with poor outcomes of malignant lymphomas not in remission treated by allogeneic HCT. (8th October 2019) - Kawajiri, Akihisa; Kitano, Shigehisa; Maeshima, Akiko Miyagi; Inamoto, Yoshihiro; Tajima, Kinuko; Takemura, Tomonari; Tanaka, Takashi; Ito, Ayumu; Okinaka, Keiji; Kurosawa, Saiko; Kim, Sung‐Won; Taniguchi, Hirokazu; et al.
Abstract: Objective: CD204 + tumor‐associated macrophages are associated with adverse outcomes of various malignancies. We performed a study to elucidate the role of CD204 + macrophages in allogeneic hematopoietic cell transplantation (allogeneic HCT). Methods: In a total of 81 patients who received allogeneic HCT for non‐remission malignant lymphoma, immunohistochemical staining of CD204 using specimens preserved before allogeneic HCT was performed. According to the average number of CD204 + macrophages in a high‐power field, patients were categorized into three groups: low (<25th percentile), intermediate (≥25th percentile and <50th percentile), and high (≥50th percentile). Results: The B‐cell lymphoma proportion was higher in the low group, while T‐cell lymphoma and adult T‐cell leukemia proportions were higher in the high group. The 3‐year overall survival (OS) was poorest in the high group; low vs intermediate vs high = 83.3% vs 43.7% vs 20.2% ( P < .01). The 3‐year cumulative incidences of relapse were significantly higher in the high group than the intermediate and low groups: 67.0% vs 38.1% vs 18.2% ( P < .01). In multivariate analyses, the numbers of CD204 + macrophages were independent risk factors of poorer OS and cumulative incidences of relapse. Conclusions: CD204 + macrophages might be associated with poorer prognosis in allogeneic HCT for malignant lymphomas.